Canva AI Interactive Quizzes to Improve Participation in Formative Assessment of Islamic Jurisprudence: A Classroom Action Research - Mutiah Farhaty; Luthfiyah Luthfiyah; Nasaruddin Nasaruddin (Universitas Islam negeri Mahmud Yunus Batusangkar, 2026)
Low student participation in formative assessment often occurs when assessment practices rely on conventional methods that are less engaging for digital-native learners. Integrating artificial intelligence–based learning media can create more interactive and motivating assessment environments. This study aims to examine the effectiveness of Canva AI interactive quizzes in improving student participation and cognitive learning outcomes in Islamic Jurisprudence (Fikih). This research employed a Classroom Action Research (CAR) design conducted in two cycles involving 78 students. Data were collected through classroom observation, learning outcome tests, and documentation of assessment activities. The results indicate a substantial increase in students’ participation and learning outcomes after the implementation of Canva AI quizzes. Quantitatively, the average score improved from 52.56% in the pre-test of Cycle I to 88.21% in the post-test of Cycle I, achieving 100% classical mastery. In Cycle II, the average score increased further to 89.36, with more students achieving perfect scores. Qualitative observations also show that the intervention successfully transformed previously passive learners into active participants during formative assessment activities. These findings suggest that Canva AI interactive quizzes serve as an effective strategy to enhance participation and engagement in Fikih learning assessments. Therefore, the integration of AI-based tools in classroom assessment is recommended to support more interactive and student-centered learning in the digital era.